About cookies on this site Our websites require some cookies to function properly (required). In addition, other cookies may be used with your consent to analyze site usage, improve the user experience and for advertising. For more information, please review your options. By visiting our website, you agree to our processing of information as described in IBM’sprivacy statement. To provide a smooth navigation, your cookie preferences will be shared across the IBM web domains listed here.
May 2003
B=3.
3 = sqrt(9)
= sqrt(1+8)
= sqrt(1+2*sqrt(16))
= sqrt(1+2*sqrt(1+15))
= sqrt(1+2*sqrt(1+3*sqrt(25)))
= sqrt(1+2*sqrt(1+3*sqrt(1+24)))
= sqrt(1+2*sqrt(1+3*sqrt(1+4*sqrt(36))))
= sqrt(1+2*sqrt(1+3*sqrt(1+4*sqrt(1+35))))
Stop after n steps to show B>f[n]:
3 = sqrt(1+2*sqrt(16)) > sqrt(1+2*sqrt(1)) = f[2]
3 = sqrt(1+2*sqrt(1+3*sqrt(25))) > sqrt(1+2*sqrt(1+3*sqrt(1))) = f[3]
To show the lower bound, consider a fixed value of n.
For k between 1 and n, define
t[k] = k*sqrt(1+(k+1)*sqrt(1+(k+2)*sqrt(...+n*sqrt(1)...)))
so that t[n]=n,
t[k]=k*sqrt(1+t[k+1])
and t[1]=f[n].
Also define r[k]=t[k]/(k*(k+2)).
Show inductively that sqrt(r[k+1])<r[k]<1.
Indeed r[n]=1/(n+2)<1, and we can calculate
k*(k+2)*r[k]=t[k]=k*sqrt(1+t[k+1])=k*sqrt(1+(k+1)*(k+3)*r[k+1]);
(k+2)**2 * r[k]**2 = 1 + (k+1)*(k+3)*r[k+1] > (1+(k+1)*(k+3))*r[k+1];
r[k]**2 > r[k+1],
and r[k]<1.
Deduce that
1 > r[1] > r[n]**(1/2**(n-1)) = 1/(n+2)**(1/2**(n-1))
0 > log r[1] > - (log(n+2)) / 2**(n-1) (natural logarithms).
Setting n=338, we estimate
log r[1] > - log(340)/2**339 > -1/(3*10**100),
and f[338]=t[1]=3*(1-r[1])>3-1/10**100, as required.
If you have any problems you think we might enjoy, please send them in. All replies should be sent to: ponder@il.ibm.com